PENENTUAN FORMULASI BAHAN TAMBAHAN SEBAGAI BAHAN BAKU SUBSTITUSI PRODUKSI TEMPE MENGGUNAKAN UJI AMBANG BATAS (THRESHOLD) DAN UJI KESUKAAN (HEDONIK) - Lya Agustina; Udiantoro Udiantoro; Suhandriyanto Suhandriyanto (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Tempe is a food fermented soy beans or other legume species using the fungus Rhizopus oligosporus and Rhizopus oryzae. By utilizing dregs tofu and mocaf expected to provide added value to the additional material and as an effort to reduce the consumption of primary ingredient in the production of tempe namely soybean. The purpose of this study was to determine the formulation of additives that are most appropriate as an additional ingredient of making tempe using threshold test and hedonic test. The test results threshold suggests that there can be found the best formulation would be expected in each type of material, the entire formulation in both types of materials response difference exceeds the prescribed limit is 50%, but each type of material has a formulation that is approaching a percentage basis, ie formulation (95: 5) on the pulp out the different response of 60% and a formulation (95: 5) on mocaf with different response of 65%. The test results hedonic showed that tempe substitutes dregs tofu most preferred is tempe with the formulation of 95: 5, while the tempe mocaf most preferred substitution is tempeh with 55:45.